1984
DOI: 10.1139/m84-195
|View full text |Cite
|
Sign up to set email alerts
|

Porcine haemophili and actinobacilli: characterization by means of API test strips and possible taxonomic implications

Abstract: Thirty Haemophilus strains and six Actinobacillus strains, all of porcine origin, were examined for their biochemical reactivity on API 20E and API ZYM test strips using dense cell suspensions (supplemented with NAD as appropriate) as strip inocula. When combined with a test for V-factor dependency, the use of both strips allowed adequate differentiation of closely related organisms. Numerical taxonomic analysis of the data demonstrated that the majority of the haemophili and actinobacilli studied could be pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The cumulative results of the biochemical testing of the isolates are presented in Table 3. The results obtained with the Sensititre system were comparable to those obtained by more traditional test methods, as reported previously (4,9,23,27,32). The biotypes of the A. suis isolates from healthy animals were virtually identical to those of clinical isolates, with the exception of esculin hydrolysis and the ability to produce acid from xylose.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The cumulative results of the biochemical testing of the isolates are presented in Table 3. The results obtained with the Sensititre system were comparable to those obtained by more traditional test methods, as reported previously (4,9,23,27,32). The biotypes of the A. suis isolates from healthy animals were virtually identical to those of clinical isolates, with the exception of esculin hydrolysis and the ability to produce acid from xylose.…”
Section: Resultssupporting
confidence: 89%
“…In the diagnostic laboratory, A. suis isolates may be identified on the basis of their hemolytic phenotype and their ability to grow on MacConkey agar; hydrolyze esculin; produce catalase, oxidase, and urease; and produce acid from arabinose, cellobiose, dextrose, lactose, melibiose, salicin, sucrose, and trehalose but not from mannitol or sorbitol (4,9,23,27,32). To date, no attempt has been made to serotype A. suis, and it is known that A. suis possesses some cross-reactive antigens including enterobacterial common antigen (6), outer membrane proteins (19), somatic antigens (29,31), and exotoxins (7,8,16).…”
mentioning
confidence: 99%
“…7,19 Cross-reactivity could be due to the close relationship of these bacteria. 11,16 In a numerical taxonomic analysis (based on the biochemical reactivity on API20E and API ZYM test strips) using dendrograms that compared the similarity of H. parasuis, A. pleuropneumoniae, Pasteurella multocida, and Bordetella bronchiseptica, a similarity of 86% between H. parasuis and A. pleuropneumoniae was found, but in some cases comparing specific strains of these bacteria similarity reached 91% and 93%. 11 However, cross-reactivity could be relatively serovar specific.…”
Section: Discussionmentioning
confidence: 99%
“…11,16 In a numerical taxonomic analysis (based on the biochemical reactivity on API20E and API ZYM test strips) using dendrograms that compared the similarity of H. parasuis, A. pleuropneumoniae, Pasteurella multocida, and Bordetella bronchiseptica, a similarity of 86% between H. parasuis and A. pleuropneumoniae was found, but in some cases comparing specific strains of these bacteria similarity reached 91% and 93%. 11 However, cross-reactivity could be relatively serovar specific. In the study in which cross-reactivity was not found, only A. pleuropneumoniae serovar 1 was tested, and the existence of cross-reactivity among tested H. parasuis serovars was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The 10 urease-negative isolates were indole positive and exhibited a pattern of carbohydrate fermentation which distinguished them from H. parasuis and Haemophilus taxon C. Differences exist in reported biochemical activity of swine haemophili (2,6,7,12,20,23). Although these varying TABLE 4.…”
Section: Pharyngeal Diverticulum M96mentioning
confidence: 99%